2015
DOI: 10.1021/jacs.5b00959
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo-Pnicta-triazanes: Biradicaloids or Zwitterions?

Abstract: Bulky triazenides were utilized in the reaction with pnictogen(III) chlorides (ECl3, E = P, As, Sb, and Bi) yielding triaza-pnicta-butene analogues of the type R-N═N-N(R)-ECl2 (R = Ter = 2,6-bis(2,4,6-trimethylphenyl)phenyl). Subsequent reduction of these dichloro-species afforded unprecedented four-membered group 15 heterocycles [E(μ-NTer)2N] bearing one dicoordinate pnictogen and nitrogen atom. These N3E rings represent species at the borderline between singlet biradicaloids and zwitterions with diminished r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 56 publications
3
57
1
1
Order By: Relevance
“…The in‐plane Sb−Cl2 bond with a length of 2.3596(4) Å is slightly shorter than the out‐of‐plane Sb−Cl1 bond 2.3835(3) Å, which can be attributed to a hyperconjugative effect of the nitrogen lone pair interacting with the parallel‐lying σ*(Sb−Cl1) orbital (38 kJ mol −1 ) according to a natural bond orbital analysis . Such delocalization effects are also known from molecules consisting of [SbCl 2 ] moieties and amindinate or guanidinate substituents, or examples from our group, for example, Ter 2 N 3 SbCl 2 and Ter 2 N 2 PSbCl 2 . The As−P bond length (As1−P1 2.1444(4) Å) is in good agreement with the expected value for a double bond (Mes*‐As=P‐Mes* 2.141(5), Σ r cov (As=P)=2.16 Å), while both the As−N and Sb−N bond lengths compare well to polarized single bonds (As−N 1.850(1), Sb−N 2.055(1); cf.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The in‐plane Sb−Cl2 bond with a length of 2.3596(4) Å is slightly shorter than the out‐of‐plane Sb−Cl1 bond 2.3835(3) Å, which can be attributed to a hyperconjugative effect of the nitrogen lone pair interacting with the parallel‐lying σ*(Sb−Cl1) orbital (38 kJ mol −1 ) according to a natural bond orbital analysis . Such delocalization effects are also known from molecules consisting of [SbCl 2 ] moieties and amindinate or guanidinate substituents, or examples from our group, for example, Ter 2 N 3 SbCl 2 and Ter 2 N 2 PSbCl 2 . The As−P bond length (As1−P1 2.1444(4) Å) is in good agreement with the expected value for a double bond (Mes*‐As=P‐Mes* 2.141(5), Σ r cov (As=P)=2.16 Å), while both the As−N and Sb−N bond lengths compare well to polarized single bonds (As−N 1.850(1), Sb−N 2.055(1); cf.…”
Section: Methodsmentioning
confidence: 98%
“…Depending on the pnictogen combination the reaction between A and ECl 3 can either result in the open‐chain species B or the cyclic species C . The concept could be applied for triazenides (E 1 =N) as well cleanly affording open‐chain species of the type TerN(ECl 2 )NNTer ( B ) and cyclic species D upon reduction …”
Section: Methodsmentioning
confidence: 99%
“…Earlier investigations had shown that biradicaloid 1 can be prepared on gram scale and that it is highly reactive,b ut stable in solution and in the solid state under argon atmosphere. [45] The 31 PNMR resonance of 2 was observed as an AA'XX' pattern centered at 193.9 ppm (Figure 1, left;f or sections of the 1 HNMR spectra, see the Supporting Information, Figure S1). Interestingly, 31 PNMR experiments indicated the presence of only one isomer of 2.…”
mentioning
confidence: 99%
“…59 Therefore, it can be deduced that the symmetrically bridging NPN ligand retains its anionic nature in the bridging mode, as indicated by these phosphorus-nitrogen bond lengths, which is similar to analogous structures with μ-N,N′ bridging complexes (cf. It is interesting to note that the isovalence-electronic triazenide species, [N(µ-NTer) 2 Sb], 62 exists as a monomeric compound and does not dimerize to form the distibenium bicyclic species. The molecular structure of heterocycle 6 is reminiscent to the (NCN) 2 P 2 scaffold of [P 2 {µ-(MesN) 2 CNMes} 2 ].…”
Section: Structure and Bonding Ofmentioning
confidence: 99%